Lord Lister No. 0012: Verzonken schatten - Matull, Kurt, 1872-1920; Blankensee, Theo von, 1881-1928 (Salt Lake City, UT : Project Gutenberg, 2022)
"Lord Lister No. 0012: Verzonken schatten" by Kurt Matull and Theo von Blankensee is a novel written in the early 20th century. The story centers around the daring adventures of Lord Lister and his friend Charly Brand as they embark on a quest for treasure linked to the ill-fated ship "Tasmania," which sunk with millions in gold aboard. This gripping tale unfolds through high-stakes scenarios filled with nautical peril, intrigue, and a dash of mystery. At the start of the book, we meet the staterooms of the steamboat "Tasmania" amid a fierce storm in the Bay of Biscay. Passengers, particularly three bank officials tasked with transporting valuable gold bars, face grave danger as the ship is jeopardized by the storm's ferocity. Just before a catastrophic collision that leads to the ship's sinking, the characters prepare a message in a sealed bottle, hoping to record the events for posterity. The narrative then shifts to an intriguing beach scene where Lord Lister discovers the message washed ashore, setting the stage for his determined quest to uncover the sunken treasures and the fate of those who perished, including a mysterious inheritance that must reach a woman named Lucie Watkins. (This is an automatically generated summary.)
Release date is 2022-05-21
The Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg
Keywords: Detective and mystery stories -- Periodicals; Dime novels -- Periodicals